Accurate position exchange of stamen and stigma by movement in opposite direction resolves the herkogamy dilemma in a protandrous plant, Ajuga decumbens (Labiatae) - Ye, Zhong-Ming (AoB Plants, 2019)
Herkogamy is an effective way to reduce sexual interference. However, the separation of stigma and anther potentially leads to a conflict because the pollen may be placed in a location on the pollinator different from the point of stigma contact, which can reduce pollination accuracy. Floral mechanisms aiming to resolve this conflict have seldom been explored. The floral biology of protandrous Ajuga decumbens was studied to uncover how the herkogamy dilemma can be resolved. Flower anthesis was divided into male, middle, female and wilting phases. The positions of stigma and stamen were dissimilar in different flower development stages. We measured the distance of the stamen and stigma to the lower corolla lip at different floral phases, which was the pollinators’ approaching way. The pollen viability, stigma receptivity, pollen removal and pollen deposition on stigma were investigated at different phases. During the male phase, the dehisced anthers were lower than the stigma, located at the pollinators’ approaching way, and dispersed most pollen with high viability. As the flower developed, the anthers moved upwards, making way for pollen deposition during the female phase. Meanwhile, the stigma becomes receptive by moving into the way and consequently was deposited with sufficient pollen. The position exchange of the stamen and stigma created a dynamic herkogamy at the floral phase with different sexual functions. This floral mechanism effectively avoided sexual interference and maintained pollination accuracy. In Ajuga, the movement herkogamy might be of adaptive significance in response to the changes in the pollination environment.